EVALUASI MANFAAT PEMBANGUNAN JALAN ALTERNATIF BERDASARKAN ANALISA CONSUMER SURPLUS PADA RUAS JALAN KUALA TUHA - LAMIE - Zahroel Barady; Muhammad Isya; Irin Caisarina (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: Roads Kuala Tuha - Lamie which located in Nagan Raya Regency is the alternative roads of cross South West in addition to the existing road of Kuala Tuha - Simpang Peut - Lamie. These alternate roads through the coastline has a total length of approximately 47.6 km. Bearing in mind the existing roads through mountainous areas with a total length of about 49.5 km and has 1.9 km distance difference. This research aims to analyze the economic feasibility of transport based on the Consumer Surplus method, public perception and analysis of sensitivity to the construction feasibility of alternative roads. The methods used to analyze the economics of transportation is the Pacific Consultant International (PCI). The results of the data analysis, the average trip time required for existing roads is 1.26 hours and alternative roads is 1.06 hour trip each time, so has the benefits of saving time from this alternative road construction is 0.20 hours for one trip. Savings time value of 23,828 IDR/hr for passenger cars, Rp. 157,812 IDR/hr for buses and 16,344 IDR/hr for trucks, while for VOC 387 IDR/km for passenger cars, 1,818 IDR/km for buses and 1,438 IDR/km for trucks. Based on the economic evaluation of road construction at the 14th year (year 2031) since the road opened already meet the standard economic feasibility with a discount rate of 10% and 12%. On discount rate 10% obtained the value of BCR and NPV is 1.24 and 39,270,069,000 IDR, at a discount rate of 12% obtained the value of BCR and NPV is 1.09 and 13,418,889,000 IDR, and the EIRR value obtained on the discount rate 13.31% or on the value of NPV = 0. There is a sensitivity analysis of parameters of NPV discount rate 10% the greatest value on the scenario I and most low on scenario VI, BCR parameter discount rate 10% and IRR the greatest value on the scenario VII and most low on the scenario I.Abstrak: Ruas jalan Kuala Tuha – Lamie terletak di Kabupaten Nagan Raya merupakan jalan alternatif lintas Barat Selatan selain ruas jalan eksisting Kuala Tuha – Simpang Peut – Lamie. Ruas jalan alternatif ini melalui pesisir pantai mempunyai panjang total sekitar 47,6 km. Mengingat ruas jalan eksisting yang melalui daerah pegunungan dengan panjang totalnya sekitar 49,5 km mempunyai selisih jarak 1,9 km. Penelitian ini bertujuan untuk menganalisis kelayakan ekonomi transportasi berdasarkan metode Consumer Surplus, persepsi masyarakat dan analisis sensitivitas terhadap kelayakan pembangunan ruas jalan alternatif. Metode yang digunakan untuk menganalisis ekonomi transportasi adalah dengan metode Pacific Consultant International (PCI). Hasil analisa data waktu perjalanan rata-rata yang dibutuhkan untuk ruas jalan eksisting adalah 1,26 jam dan untuk ruas jalan alternatif adalah 1,06 jam setiap kali perjalanan, sehingga mempunyai manfaat penghematan waktu dari pembangunan jalan alternatif ini adalah 0,20 jam setiap kali perjalanan. Penghematan nilai waktu sebesar Rp. 23.828/jam untuk mobil penumpang, Rp. 157.812/jam untuk bus dan Rp. 16.344/jam untuk truk, sedangkan untuk BOK sebesar Rp. 387/km untuk mobil penumpang, Rp. 1.818/km untuk bus dan Rp. 1.438/km untuk truk. Berdasarkan evaluasi ekonomi pembangunan jalan ini pada tahun ke 14 (tahun 2031) sejak jalan dibuka sudah memenuhi standard kelayakan ekonomi dengan discount rate 10% dan 12%. Pada discount rate 10% didapat nilai BCR 1,24, NPV Rp. 39.270.069.000, pada discount rate 12% didapat nilai BCR 1,09, NPV Rp. 13.418.889.000, dan nilai EIRR didapat pada discount rate 13,31% atau pada nilai NPV = 0. Analisis sensitivitas terdapat parameter NPV discount rate 10% nilai yang paling besar pada skenario I dan paling rendah pada skenario VI, parameter BCR discount rate 10% dan IRR nilai yang paling besar pada skenario VII dan paling rendah pada skenario I.